External beam radiotherapy facilities in Ukraine. Trends and challenges - Starenkiy, V.P.; Petrichenko, O.O.; Averyanova, L.O. (Вопросы атомной науки и техники, 2017)
The most important aspects of technological support of the radiation therapy of Ukraine are considered in accordance with the requirements of the IAEA. The reasons that influence the availability of radiotherapy for cancer patients in Ukraine are analyzed taking into account the experience of Grigoriev Institute for Medical Radiology of the National Academy of Medical Sciences of Ukraine.